Multifaceted Comparison of Two Cryotherapy Devices Used After Total Knee Arthroplasty: Cryotherapy Device Comparison. (September 2016) - Schinsky, Mark F.; McCune, Christine; Bonomi, Judith
Abstract : BACKGROUND: Some form of cryotherapy used after total knee arthroplasty is commonplace. However, various factors determine the specific device deployed. PURPOSE: This study aimed to answer the following questions: Is an ice/gel pack cryotherapy wrap noninferior to a more elaborate circulating cold water therapy device in terms of patient outcomes, patient satisfaction, and hospital staff satisfaction? What is the projected economic impact of using an ice/gel pack cryotherapy wrap versus a circulating cold water cryotherapy device? METHODS: A group of 100 patients undergoing primary total knee arthroplasty by a single surgeon were enrolled in an institutional review board–approved, prospective study and randomized to receive either a circulating cold water or ice/gel pack cryotherapy device postoperatively. Demographic, pain, swelling, blood loss, range of motion, compliance, satisfaction, and adverse event outcomes were recorded until 6 weeks after surgery. Hospital staff satisfaction and economic variables were examined. RESULTS: The ice/gel pack cryotherapy wrap was noninferior to the cold water cryotherapy device for any patient outcome measured. Average pain level at 6 weeks postoperative was significantly less in the ice/gel pack cryotherapy wrap group. Hospital staff satisfaction was higher with the ice/gel pack cryotherapy wrap. Substantial economic savings can be realized at our institution by switching to the lower cost cryotherapy device. CONCLUSION: In this study, the lower cost ice/gel pack cryotherapy wrap was noninferior to the circulating ice water cryotherapy device with respect to objective patient outcomes and subjective patient satisfaction after total knee arthroplasty. Hospital staff satisfaction and economic considerations also favor the ice/gel pack compression cryotherapy wraps.